An infrared and raman spectroscopic study on some 3,5-lutidine metal(II) tetracyanonickelate complexes - Yurdakul, S.; Davies, J. Eric D.; AKYÜZ, SEVİM (Elsevier, 1987)
The results of an infrared and Raman spectroscopic study are presented for seven new metal(II) 3,5-lutidine tetracyanonickelate complexes, ML2Ni(CN)4 [where L = 3.5-di-methylpyridine or 3,5-lutidine; M = Mn, Fe, Co, Ni, Cu, Zn or Cd]. Their structure consists of polymeric layers of [MNi(CN)4]∞ with the 3,5-lutidine molecules bound directly to the metal (M). The copper complex has spectral features different from the other six compounds. The effective magnetic moments of the complexes are also given.